Abuse experiences and it's relationship to aggressive behavior Among A Sample of Orphans children in Hama city schools (Journal of Hama University, 2022)
This research aims at present to detective the correlation between Abuse experiences and aggressive behavior, as well as to detect differences between the average scores children at the scale of Abuse experiences and the scale of aggressive behavior according to the (sort of deprivation) variable among orphans children in Hama city schools. To achieve this goal has been to use the following tools: scale to measure the Abuse experiences and scale of perceived aggressive behavior and both of scales were preparation by the researcher. The study sample consists of (120) male and female orphans in Hama city schools.The most important findings of Search:• The level of spread of abuse experiences among the research sample members falls within the average limits on the scale as a whole.• There were correlations statistically significant between the scores of children on the Abuse experiences and aggressive behavior.• There were differences between the mean scores of children on the scale of Abuse experiences due to the sort of deprivation variable favor for deprivation of mother.• There were differences between the mean scores of children on the scale of aggressive behavior due to the sort of deprivation variable favor for deprivation of father.
Keywords: Abuse experiences, aggressive behavior, the orphans' children in Hama city schools.